Analisis Yuridis Perbuatan Melawan Hukum pada Penguasaan Tanah Tanpa Hak (Putusan Nomor 115/PDT.G/2023/PN TJK) - Rahmat Akbar Aiedil; Depri Liber Sonata; Dita Febrianto; Selvia Oktaviana; Harsa Wahyu Ramadhan (Lembaga Yasin AlSys, 2026)
Although land disputes frequently occur, studies that specifically discuss the clash of claims between a good-faith purchaser in an underhand sale and the seller’s heirs who base their claim on a will remain limited. This study aims to analyze the fulfillment of the elements of an Unlawful Act (Perbuatan Melawan Hukum [PMH]), the legal considerations of the panel of judges, and the legal consequences of Decision of the Tanjung Karang District Court Number 115/Pdt.G/2023/PN Tjk. This study employed a normative legal approach with a judicial case study design. Data were collected through library research and document study covering primary, secondary, and tertiary legal materials, and were then analyzed qualitatively. The results showed that the heirs’ act of continuing to physically control the land unilaterally fulfilled all elements of an Unlawful Act as regulated in Article 1365 of the Indonesian Civil Code. The judges’ considerations emphasized the evidentiary strength of the payment receipt and certificate compared with the argument based on a unilateral will, although the claims for compensation and dwangsom were rejected because they were not supported by proof of actual loss. These findings affirm that a sale and purchase that has been fully paid has legally binding force and can nullify conflicting inheritance claims, while also strengthening the application of the nemo plus juris principle in the settlement of ownership disputes. The implications of this study indicate the importance of legal protection for good-faith purchasers as well as the need for the prompt registration of transfer of rights to minimize similar disputes in the future. Keywords: Nemo Plus Juris Principle; Good-Faith Purchaser; Unlawful Possession; Unlawful Act; Land Dispute